Cross domain self-monitoring in anosognosia for memory loss in Alzheimer's disease. (April 2018) - Chapman, Silvia; Colvin, Leigh E.; Vuorre, Matti; Cocchini, Gianna; Metcalfe, Janet; Huey, Edward D.; Cosentino, Stephanie
Abstract: Anosognosia for memory loss is a common feature of Alzheimer's disease (AD). Recent theories have proposed that anosognosia, a disruption in awareness at a global level, may reflect specific deficits in self-monitoring, or local awareness. Though anosognosia for memory loss has been shown to relate to memory self-monitoring, it is not clear if it relates to self-monitoring deficits in other domains (i.e., motor). The current study examined this question by analyzing the relationship between anosognosia for memory loss, memory monitoring, and motor monitoring in 35 individuals with mild to moderate AD. Anosognosia was assessed via clinical interview before participants completed a metamemory task to measure memory monitoring, and a computerized agency task to measure motor monitoring. Cognitive and psychological measures included memory, executive functions, and mood. Memory monitoring was associated with motor monitoring; however, anosognosia was associated only with memory monitoring, and not motor monitoring. Cognition and mood related differently to each measure of self-awareness. Results are interpreted within a hierarchical model of awareness in which local self-monitoring processes are associated across domain, but appear to only contribute to a global level awareness in a domain-specific fashion.